The accuracy of prenatal ultrasound in determining the type of orofacial cleft. (6th April 2015) - Loozen, C. S.; Maarse, W.; Manten, G. T. R.; Pistorius, L.; Breugem, C. C.
Abstract Objective The aim of this study was to assess the accuracy of prenatal transabdominal ultrasound in determining the oral cleft type. Methods A retrospective cohort study was performed on all consecutive cases of orofacial cleft diagnosed by prenatal ultrasound examination in the Wilhelmina Children's Hospital, a tertiary referral hospital, between January 2002 and December 2012. Prenatal findings were compared with postnatal diagnoses. Results A total of 134 patients were included. The mean gestational age at ultrasound examination was 24 weeks + 5 days. Prenatal diagnosis was in accordance with postnatal findings in 76.9% of the cases (103/134) with regard to the cleft type. Underestimation of the cleft occurred in 19.4% (26/134), whereas in 3.7% (5/134), the extent was overestimated. In distinguishing bilateral from unilateral clefts, no errors were made. Conclusion Prenatal ultrasound is accurate in assessing the types of orofacial clefts in a large majority of the cases and is completely accurate in distinguishing between unilateral and bilateral clefts. This study indicates that it is a reliable technique to assess the cleft type, which is important for counseling future parents. Although, the clinician should be aware of the fact that a cleft palate is easily missed, and subsequently, underestimation of cleft extend is frequent. © 2015 John Wiley & Sons, Ltd.